School Improvement Policy--Site-Based Management - Tanner, C. Kenneth; Stone, Cheryl D. (Education Policy Analysis Archives, 1998)
Have administrative functions of principals changed in schools practicing site-based management (SBM) with shared governance? To deal with this issue we employed the Delphi technique and a panel of 24 experts from 14 states. The experts, which included educational specialists, researchers, writers, and elementary school principals, agreed that the implementation of SBM dramatically influences the roles of the principal in management/administration and leadership. Data revealed that the elementary principal's leadership role requires specialized skills to support shared governance, making it necessary to form professional development programs that adapt to innovations evolving from the implementation of SBM.